Work stress and cortisol level among shift workers in a tyre manufacturing factory in Selangor - Md. Nasir, Nasimah; Hashim, Zailina (Environmental and Occupational Health Society, 2016)
Objective: A study was conducted to examine associations between work stress and cortisol hormone level among shift worker at a tyre manufacturing factory in Selangor.